Connect Farmer - V.Juno Bella Gracia, S; M.R, Sonali; N, Sowmya; P, Suja (International Journal of Engineering and Technology, 2018)
The issues faced by farmers has become the most paramount in these days, especially towards their profit rate. We intend to create an application in order to connect the farmers and the retailers directly and to provide regional languages for the farmers automatically, based on the location detected through GPS. This application also provides facility to farmers for buying seeds, fertilizers and pesticides. It also notifies to consumer and retailer about the amount of pesticides used.Â